High-efficiency optical gain in type-ii semiconductor nanocrystals of alloyed colloidal quantum wells - Guzelturk, Burak (2020)
Colloidal nanocrystals having controlled size, tailored shape, and tuned composition have been explored for optical gain and lasing. Among these, nanocrystals having Type-II electronic structure have been introduced toward low-threshold gain. However, to date, their performance has remained severely limited due to diminishing oscillator strength and modest absorption cross-section. Overcoming these problems, here we realize highly efficient optical gain in Type-II nanocrystals by using alloyed colloidal quantum wells. With composition-tuned core/alloyed-crown CdSe/CdSexTe1-x quantum wells, we achieved amplified spontaneous emission thresholds as low as 26 μJ/cm2, long optical gain lifetimes (τgain ≈ 400 ps), and high modal gain coefficients (gmodal ≈ 930 cm-1). We uncover that the optical gain in these Type-II quantum wells arises from the excitations localized to the alloyed-crown region that are electronically coupled to the charge-transfer state. These alloyed heteronanostructures exhibiting remarkable optical gain performance are expected to be highly appealing for future display and lighting technologies.